Stud attachments used in tooth-supported overdenture - ÖZKAN, YASEMİN; GÖZNELİ, RİFAT (Springer Nature, 2023)
Stud attachments are the most popular and most accessible type of attachments to be used primarily for overdenture among other attachments and available on the market for several decades. Stud attachments are placed directly on the tooth/root or attached (indirectly) to the cast copings for improving both retention and stability. They are straightforward to use and provide reasonable retention and stability for implant overdentures. Also, they are low in profile to reduce leverage upon the retaining abutments, are comfortable for the patient to maintain hygiene, allow independent physiologic movement of abutments, and are easy to repair. Stud attachments may be extraradicular or intraradicular and they may also be classified as resilient and rigid attachments. The resilient attachments permit some vertical and rotational movements on soft tissue for protecting the underlying abutments or implants against overload. Also, the resilient attachments permit vertical movement during mastication, reducing stress transfer to the abutments (stress-breaking function) and transmitting the forces to the residual ridge acting as stress transmitters. However, the resilient attachments usually require space and might cause posterior mandibular resorption with the vertical movement of the denture. On the other hand, the non-resilient (rigid) type does not permit any movement of the overdenture during the function.
Keywords: Diş Hekimliği; Klinik Bilimler; Protetik Diş Tedavisi; Sağlık Bilimleri; Dentistry; Clinical Sciences; Prosthetic Dentistry; Health Sciences; Klinik Tıp (MED); Klinik Tıp; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; Clinical Medicine (MED); CLINICAL MEDICINE; DENTISTRY, ORAL SURGERY & MEDICINE; Periodontoloji; Ortodonti; Ağız Cerrahisi; Diş Hijyeni; Dişçilik Hizmetleri; Diş Hekimliği (çeşitli); Periodontics; Orthodontics; Oral Surgery; Dental Hygiene; Dental Assisting; Dentistry (miscellaneous); General Dentistry